PLANTAR FASCIITIS TREATMENT WITH PLATELET-RICH PLASMA INJECTION VERSUS STEROID INJECTION - SRIVASTAVA, VASU; VISHWAS; RATHI, RAHUL; MEENA, LAXMI NARAYAN; KUMAR, B. L. (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Plantar fasciitis is characterized by heel pain that worsens when you bear weight after a long period of rest. Injections of steroids are one of the numerous therapeutic techniques that are frequently used to control plantar fasciitis. Numerous studies demonstrate that short-term pain alleviation with steroid injections is not long-lasting. According to recent studies, autologous platelet-rich plasma (PRP) injections encourage healing, which improves both short- and long-term pain alleviation. To compare the effects of local PRP injection and corticosteroid in the management of chronic plantar fasciitis, the current study was conducted. Methods: Sixty patients who met the criteria for this prospective double-blind trial were randomly assigned to one of two groups. Patients in Group I received an injection of steroid, whereas those in Group II received an injection of PRPs. The PNS numerical pain score (NPS) and a visual analog scale (VAS) were used to evaluate the patients. An evaluation was conducted before the injection as well as at 6 weeks, 3 months, and 6 months after the injection. Results: The mean VAS in Group I reduced from 7.00 before injection to 2.31 and that in Group II decreased from 7.81 before injection to 1.12. At the 6-month follow-up, the mean NPS score in Group I increased from 7.05 to 1.41 and in Group II from 7.86 to 1.02. The VAS and NPS improvements were statistically significant. In both groups, the plantar fascia thickness had decreased at the conclusion of the 6-month follow-up period (5.88 mm in Group I to 4.03 mm and 5.96 mm to 3.27mm in Group II), and the difference was statistically significant. Conclusion: When compared to steroid injection, local PRP injection is an excellent therapeutic option for persistent plantar fasciitis with long-lasting positive effects.